CD134L expression on dendritic cells in the mesenteric lymph nodes drives colitis in T cell-restored SCID mice. - Malmström, V; Shipton, D; Singh, B; Al-Shamkhani, A; Puklavec, M; Barclay, N; Powrie, F (2001)
Transfer of CD45RB(high) CD4+ T cells to immune-deficient mice in the absence of regulatory T cells leads to a Th1-mediated colitis. In this study, we show that intestinal inflammation is characterized by a 15-fold increase in the number of CD134L+ (OX40L+)-activated DC in the mesenteric lymph nodes (MLNs) compared with BALB/c mice. This was important functionally, as administration of an anti-CD134L mAb inhibited the proliferation of T cells in the MLNs as well as their expression of the gut-homing integrin alpha(4)beta(7). Most importantly, the anti-CD134L mAb completely blocked development of colitis. Surprisingly, CD134L was found to be expressed by a proportion of dendritic cells (DC) in the MLNs of unreconstituted SCID mice, suggesting that CD134L can be induced on DC in the absence of T cell-derived signals. These results indicate that some DC in the MLNs of SCID mice express an activated phenotype and that CD134L expression by these cells is involved in the development of colitis induced by T cell transfer. Accumulation of CD134L+ DC was inhibited by cotransfer of regulatory T cells, suggesting that inhibition of the accumulation of activated DC is one mechanism by which these cells prevent immune pathology.